Conversion in the age of pluralism - Giordan, Giuseppe. (Religion and the Social Order, 2009)
The theme of conversion constitutes a privileged point to study the framework linking an individual to the sociocultural contexts in which he or she is included. Changes in personal biographies and sociocultural change are interwoven when we speak of conversion: values, speech, norms, behaviors, beliefs, lifestyles, interests--everything is open to potential debate when an individual \'converts.\' Conversion is especially developed here through a connection with the dynamics of pluralism, which appears to be the most peculiar cultural characteristic of our era: what does it mean to speak of \'conversion\' in a time in which it seems that the presumption of only one \'true\' truth no longer exists, while instead many different truths live together, each with its own judgment criteria.